A 2000 Social Accounting Matrix for El Salvador - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The 2000 Social Accounting Matrix (SAM) for El Salvador was constructed following the Central Bank Input-Output Matrix (IOM) for year 2000 and includes 45 production sectors in the economy. Factors were divided in eighteen groups: capital, land, and sixteen categories of labor. The labor force was divided into skilled and unskilled labor, both disaggregated by whether a person works in the tradables or nontradables sector, whether he/she works in an urban or rural area, and by gender. Institutions were comprised of households, the government, an enterprise account and the rest of the world. Households were divided into four categories according to degree of urbanization and educational level of the head of household: urban/rural families whose head has/has not completed at least ninth grade.